Leveraging Microcontroller-Based approach on Automatic pH Control, Monitoring, and Feeding System for Catfish Aquaculture. - Ahmad Nurul Azmi; Mohammad Hafiz Hersyah (JITCE (Journal of Information Technology and Computer Engineering), 2025)
Fisheries cultivation is beginning to experience improvement and enthusiasm within the community. Especially the cultivation of catfish, which is gaining quite a lot of enthusiasts. This is caused by catfish that are easy to cultivate, have high demand within the community, and are rich in protein. The increase in catfish enthusiasts is based on the period from 2018 to 2019, during which the growth of catfish has increased by 27.76%. The increase in catfish production reached 1,005,530 tonnes in 2018 and 1,224,360 tonnes in 2019.Along with the advancements in technology for cultivating feed catfish, which meet the energy and growth needs, there should be sufficient resources to achieve a maximum harvest. However, lately, many cultivators have failed. This is due to several problems, including the intensity of irregular feeding and unstable catfish pool water levels, which resulted in the growth of catfish not yet fully implemented by cultivators. Consequently, many catfish cultivators suffered losses. Technology will help improve the quality of catfish feed. The basic principle of catfish cultivation is how the system can maintain a suitable water quality for catfish so that the risk of death does not occur because too Low or too high pH can have a harmful effect on catfish. pH itself is the degree of acidity used to declare the level of acidity or pH that a solution has. The components used in the design of this tool include pH sensors to read acid levels in catfish pool water, selenoids for controlling the flow of pH-adjusted liquid, load cell sensors for calculating the weight of the feed, and a servomotor to open the fish feed valve